1999
DOI: 10.1192/bjp.175.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Burden experienced by care-givers of persons with bipolar affective disorder

Abstract: Care-givers of patients with bipolar illness report widespread burden that is influenced by beliefs about the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
140
2
18

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(170 citation statements)
references
References 16 publications
10
140
2
18
Order By: Relevance
“…In our study we found quality of life to be moderately low in the caregivers. This is similar to the findings by Allison M. R. Lee et al [12], Perlick DA et al [13], , M. Reinares et al [14], Ogilvie AD et al [15], Heru AM et al [16], S.Chakrabarti et al [6], D Perlick et al [17] who have reported moderate to high levels of burden among caregivers of Bipolar patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study we found quality of life to be moderately low in the caregivers. This is similar to the findings by Allison M. R. Lee et al [12], Perlick DA et al [13], , M. Reinares et al [14], Ogilvie AD et al [15], Heru AM et al [16], S.Chakrabarti et al [6], D Perlick et al [17] who have reported moderate to high levels of burden among caregivers of Bipolar patients.…”
Section: Discussionsupporting
confidence: 81%
“…Perlick DA et al [13] found that 89%, 52%, and 61% of caregivers, respectively, experienced moderate or higher burden in relation to patient problem behaviors, role dysfunction, or disruption of household routine. S.Chakrabarti et al [17], T Y G Van Der Voort et al [22] found severity of illness among patients to be correlated consistently with severity of burden in caregivers. M. Reinares et al [14] reported that caregiver's highest subjective burden was associated with patient's hyperactivity and irritability.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical features might induce dysfunctional parental attitudes and this burden is likely to lead to inappropriate discipline and in certain conditions to abuse. Furthermore, caregivers of bipolar patients exhibit high levels of expressed emotion, including critical, hostile, or over-involved attitudes (Heru & Ryan, 2004;Ogilvie, Morant, & Goodwin, 2005;Perlick et al, 1999;Romero, Delbello, Soutullo, Stanford, & Strakowski, 2005). Finally, the association between emotional abuse and bipolar disorder might be related to parental psychopathological traits.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers asked for consent to provide written materials about the research project to relatives/closest reference persons identified by the patient (note: patients with co-morbid neurological and severe medical disorders were excuded). Each relative met at least three of the following eligibility criteria (Perlick et al 1999): parent or spouse/ partner or sibling or child of the patient, person providing the most frequent contacts with the patient, person who will be informed by the caring institution in case of any emergency, person assisting the patient in dealing with financial issues and person who most frequently accompanies the patient to medical treatments. For study inclusion the patient and at least one of the eligible relatives/closest reference persons provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The number of such studies is still insufficient, however, and most have only interviewed relatives of patients with schizophrenic disorders. In consideration of the prevalence of patients with chronic affective disorders (e.g., Jacobi et al 2004) and the increasing evidence on the burden of relatives when informally taking care of patients with recurrent depressive and bipolar disorders (e.g., Jenkins and Schumacher 1999;Mueser et al 1996;Perlick et al 1999;Schmid et al 2007), there is a clear need for such research in these groups of relatives.…”
Section: Introductionmentioning
confidence: 99%